2020
DOI: 10.17269/s41997-020-00332-3
|View full text |Cite
|
Sign up to set email alerts
|

Trends in HIV pre-exposure prophylaxis uptake in Ontario, Canada, and impact of policy changes: a population-based analysis of projected pharmacy data (2015–2018)

Abstract: Objectives HIV pre-exposure prophylaxis (PrEP) is a proven tool for HIV prevention, but PrEP use in Ontario, Canada, and the effects of recent policies are unknown. We estimated the number and characteristics of PrEP users in Ontario and evaluated the impacts of policy changes between July 2015 and June 2018. Methods We obtained tenofovir disoproxil fumarate/emtricitabine (TDF/FTC) dispensation data for Ontario from IQVIA, and applied an algorithm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 18 publications
(19 reference statements)
0
20
0
4
Order By: Relevance
“…To date, available data on PrEP use in real-life were restricted to specific subgroups in France. 23 , 32 , 34 Several representative studies on PrEP use and users characteristics were conducted in other countries 35 , 36 , 37 , 38 , 39 , 40 but did not cover the period of the COVID-19 pandemic which had a significant impact on access to prevention services, including PrEP. 11 , 12 , 13 Large scale, real-life studies assessing PrEP number of users and patterns of use, such the one presented here, are essential to guide health authorities in promoting the use of PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…To date, available data on PrEP use in real-life were restricted to specific subgroups in France. 23 , 32 , 34 Several representative studies on PrEP use and users characteristics were conducted in other countries 35 , 36 , 37 , 38 , 39 , 40 but did not cover the period of the COVID-19 pandemic which had a significant impact on access to prevention services, including PrEP. 11 , 12 , 13 Large scale, real-life studies assessing PrEP number of users and patterns of use, such the one presented here, are essential to guide health authorities in promoting the use of PrEP.…”
Section: Discussionmentioning
confidence: 99%
“…Provincial (D. Tan et al., 2019) estimates suggest that based on PrEP initiation criteria, upward of 30,000 gay, bisexual, and other men who have sex with men in Ontario may benefit from this strategy. This is a large population which cannot be adequately served by a limited number of specialists and would benefit from a decentralized, community-based approach to PEP and PrEP delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, PrEP/PEP is prescribed in a “centralized” way, meaning by a limited number of HIV specialists. It is estimated that over 30,000 individuals in Ontario meet guideline indications for PrEP, but only approximately 4000 are currently receiving it, despite the availability of generic TDF/FTC and this medication’s listing on the Ontario Drug Benefit in September of 2017 (D. Tan et al., 2019). This approach is inadequate to meet the growing demand for PrEP/PEP, is costly, and detracts from these specialists’ ability to care for those already living with HIV.…”
Section: Background and Purposementioning
confidence: 99%
“…Preexposure prophylaxis was used off label until Health Canada approved daily TDF/FTC for PrEP in 2016, lowercost generic versions became available in 2017 and the Canadian guideline was released in 2017. 2,6,32 A study of prescription data in 8 provinces estimated that 9657 patients were receiving PrEP in 2018, about 98% of whom identified as male. 32 from 44.9% to 58.1%, yet only 14.5%-21.8% had used PrEP.…”
Section: What Proportion Of Eligible Patients In Canada Are Taking Pr...mentioning
confidence: 99%
“…1 Preexposure prophylaxis (PrEP) is an important means of preventing acquisition of HIV; however, it is underused. [2][3][4] Although generalists (e.g., family physicians, nurse practitioners and general internists) could play a vital role in implementing PrEP, a recent small survey of general practitioners in Nova Sco tia found that most did not prescribe PrEP. 5 We describe PrEP for HIV and discuss current uptake and potential barriers to its use, as well as the approach to prescribing PrEP (Box 1).…”
mentioning
confidence: 99%